THE EFFECT OF COOPERATIVE LEARNING STRATEGY STAD MODEL IN LEARNING HIGH SCHOOL PHYSICS - Latif, Anik Nurul; Nisa, Zakiyatun; Hidayatullah, Ahmad Fauzan (Universitas Negeri Medan, 2024)
This study aims to analyze and determine the effect of the STAD type cooperative learning strategy model on preschool physics education. On the one hand, surveys are conducted in the online library research process, and on the other hand, information is collected by browsing through magazines, books and based on the research conducted. The results show the effectiveness of the STAD cooperative learning strategy in high school physics education could improve students' cooperative abilities and interactive abilities between students. Teachers can actively activate and develop students' unique skills. Another effect is the achievement of academic achievement increases compared to before.Keywords: Cooperative Learning, STAD Model, Learning, Strategy